Words Matter: Peer Review as a Failing Safeguard - Tom Quiggin (Perspectives on Terrorism)
Peer review is intended to support the quality and standards of academic work.  The peer review process has been questioned recently in a number of different arenas.  Source reliability and information credibility can be a problem when an academic scholar or an academic product steps into the public realm through a court case.  In these circumstances, it is not just the credibility of the academic community that is being tested: lives and liberty can be at stake.  Peer-reviewed article must provide a basic standard of trustworthiness.  At a minimum, the peer review process, though a fact checking process, should be able to assure the reader that the sources of the information are reliable and the information provided is credible.